2010
DOI: 10.1111/j.1365-2621.2010.02224.x
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of chemical components in oolong tea in relation to perceived quality

Abstract: Properties of leaf and infusion colours, chemical components and volatile flavour compounds of oolong teas and their correlation with perceived quality score given by tea-tasting panel were analysed. The scores for appearance and infused leaf correlated strongly with concentrations of chlorophyll a (chl a), chlorophyll (chl b) and chlorophyll (chl) (r = 0.355-0.433, P < 0.05) and the total quality score (TQS) positively correlated with concentrations of chl a, chl b and chl (r = 0.517-0.533, P < 0.01). The per… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
43
0

Year Published

2012
2012
2020
2020

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 50 publications
(48 citation statements)
references
References 25 publications
(51 reference statements)
5
43
0
Order By: Relevance
“…OAV analysis showed that octanal, 2‐pentyl‐furan, trans‐ nerolidol, benzene acetaldehyde, and 2‐ethyl‐furan had high OAV values in the NIOT sample (Table ). This phenomenon was consistent with a previous study that the chemicals such as nerolidol and phenyl acetaldehyde were the characteristic aroma compounds of Oolong tea (Wang et al, ). Besides, the OIOT showed higher OAVs of β ‐trans‐ damascenone (OAVs of 22,543.7 vs. 0.0) and octanal (OAVs of 59,529.0 vs. 31,294.1) than the NIOT (Table ), which might explain why the OIOT had much stronger intensities of sweet and fruit notes (Table ), since these chemicals possess honey‐like and fruity notes (Zhu et al, ).…”
Section: Resultssupporting
confidence: 93%
See 1 more Smart Citation
“…OAV analysis showed that octanal, 2‐pentyl‐furan, trans‐ nerolidol, benzene acetaldehyde, and 2‐ethyl‐furan had high OAV values in the NIOT sample (Table ). This phenomenon was consistent with a previous study that the chemicals such as nerolidol and phenyl acetaldehyde were the characteristic aroma compounds of Oolong tea (Wang et al, ). Besides, the OIOT showed higher OAVs of β ‐trans‐ damascenone (OAVs of 22,543.7 vs. 0.0) and octanal (OAVs of 59,529.0 vs. 31,294.1) than the NIOT (Table ), which might explain why the OIOT had much stronger intensities of sweet and fruit notes (Table ), since these chemicals possess honey‐like and fruity notes (Zhu et al, ).…”
Section: Resultssupporting
confidence: 93%
“…The NIOT and OIOT had 28 and 23 volatiles detected (Table ), respectively. Specifically, trans‐ nerolidol (10,660.7 μg/ml), indole (4,778.1 μg/ml), α ‐ farnesene (4,507.8 μg/ml), phenyl acetaldehyde (2,034.0 μg/ml), hexanal (1,986.9 μg/ml), and 2 ‐ pentyl‐furan (1,403.1 μg/ml) had higher concentrations than other volatiles in the NIOT (Table ), which was consistent with the previous report that nerolidol, indole, benzene acetaldehyde, linalool, linalool oxide, hexanal, benzyl nitrile, and geraniol were the prevailing volatile compounds in Oolong tea (Wang et al, ). The main volatile constituents of OIOT were 3,5‐dimethyl‐phenol (668.5 μg/ml), 3,7‐dimethyl‐1,5,7‐octatrien‐3‐ol (482.9 μg/ml), 2‐methyl‐furan (479.9 μg/ml), and octanal (416.7 μg/ml).…”
Section: Resultssupporting
confidence: 80%
“…Linalool and nonanal have been characterized as aroma-active compounds contributing to floral or fruity odors in Longjing tea infusions (Table 2), and linalool has a high flavor dilution (FD) factor ≥100 (Kumazawa and Masuda, 1999;Cheng et al, 2008). Furthermore, they were also reported to have significant positive correlation with the perceived aroma of Longjing tea or oolong tea (Wang and Ruan, 2009; Wang et al, 2010). Safranal was also characterized as an herbal odorant in green tea (Zhu et al, 2008) and Pu-erh tea (Lv et al, 2012).…”
Section: Volatile Compounds and Perceived Aroma Qualitymentioning
confidence: 94%
“…Polyphenols are widely used for prophylaxis and treatment of a variety of disorders. Lipid is also necessary though lipids are not major constituents in a tea brew but they can play an important roles in the development of aroma (Bhuyan et al 1989, Hara et al 1995, Scharbert and Hofmann 2005, Wang and Ruan 2009 and has an impact on nutritional profile of tea. however, there is no absolute measurement of caffeine, polyphenol and crude fat content of the released BT varieties.…”
mentioning
confidence: 99%